A study on customer awareness and satisfaction towards Bai al'inah concept and services provided by Bank Rakyat, Jengka Branch / Siti Hajar Abdul Hamid - Abdul Hamid, Siti Hajar (Faculty of Business and Management, 2005)
The purpose of this research is to study on customers' awareness and satisfaction towards Bai Al'inah concept and service provided by Bank Rakyat Jengka Branch. Bank Rakyat was familiar with personal loan (AI’ Inah financing) among the customers. Therefore, the question is the customers understand or not actually the concept. There is one of purpose of this study. Banking offered the same products and services. The study on AI’ Inah is important to know their strength and weaknesses to make sure the customers satisfy with Bank Rakyat Jengka process. The customer will satisfy when attractive rates are offered a good quality and services. Beside that, this study evaluates the effectiveness of promotional efforts by Bank Rakyat Jengka. There is also to study from the customer opinion for the most effective tools promotion. So, Bank Rakyat can be compare their promotion activities and customer promotion tools based on customer view. For the purpose of this study the exploratory research was used. Convenience sampling size has been utilized with 100 respondents as the sample size. Questionnaires were distributed as the survey instrument, besides conducting interviews as the source of primary data other reliable resources would serve as secondary. The data will interpret by using the SPSS program.